1992
DOI: 10.1002/ps.2780360108
|View full text |Cite
|
Sign up to set email alerts
|

Spider webs are efficient collectors of agrochemical spray

Abstract: Spiders are important arthropod predators in natural and agricultural environments. This laboratory study aims to determine the uptake of agrochemical spray by orb webs. Orbs of Araneus diadematus were exposed under controlled conditions to sprays of variable pressure, volume, forward speed and droplet size.Using a tracer dye we determined, by photospectrometry, the amount of spray collected under different conditions which enabled us to calculate the exact volume collected by webs. The spraying treatment simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 10 publications
1
17
0
1
Order By: Relevance
“…Overall, statistical analysis has also indicated significant differences between pine trees and broadleaves except at the 1.5 m s −1 wind speed. This confirms previous research that narrow targets are effective in capturing small droplets (Fox RD, pers comm, 1998, and References20–23). It is interesting to note that Miles et al 20 reported that an increase in Reynolds number or Froude number increases deposition efficiency on vertical surfaces for a constant droplet size to target size ratio.…”
Section: Resultssupporting
confidence: 89%
“…Overall, statistical analysis has also indicated significant differences between pine trees and broadleaves except at the 1.5 m s −1 wind speed. This confirms previous research that narrow targets are effective in capturing small droplets (Fox RD, pers comm, 1998, and References20–23). It is interesting to note that Miles et al 20 reported that an increase in Reynolds number or Froude number increases deposition efficiency on vertical surfaces for a constant droplet size to target size ratio.…”
Section: Resultssupporting
confidence: 89%
“…Conforme Young & Edwards (1990), esses aspectos são sufi cientes para ocasionar um número relativamente menor de indivíduos desse grupo em um ambiente. De modo geral, pomares orgânicos facilitam a presença e abundância das aranhas, em especial das caçadoras errantes, as quais, conforme Amalin & Peña (1999), são mais suscetíveis aos compostos químicos aplicados, por percorrerem a copa ativamente, estando assim mais vulneráveis; contrariamente ao afi rmado por Samu et al (1992), de que as construtoras, por apresentarem o hábito de eventualmente ingerir partes da teia, seriam as mais atingidas.…”
Section: Resultsunclassified
“…EVERTS et al, 1991). Furthermore, sublethal doses can change or temporarily prevent the webbuilding behaviour of spiders (SAMU and VOLLRATH, 1992).…”
Section: Pesticide Side-effectsmentioning
confidence: 99%
“…Because spiders live in the vegetation layer and are active during and after spraying, they are easily exposed to pesticides (JEPSON, 1989). Furthermore, their webs are excellent collectors of pesticide spray (SAMU et al, 1992).…”
Section: Pesticide Side-effectsmentioning
confidence: 99%